The Book Museum: Some Problematic Theoretical and Historical Aspects - Braziūnienė, Alma (Knygotyra, 2018)
[full article and abstract in Lithuanian; abstract in English]The article deals with the problematic theoretical aspects of book museums (their functions, types, specificity in the context of other museums, similarities with the library divisions of documentary heritage) and examines the issues related to the establishment, development, registration and spread of book museums in Europe in the second half of the 20th century. It has been discovered that although the functions of the book museum and the special documentary heritage library divisions (Rare Books and Manuscript Divisions) are very similar or even overlap (preservation, study and actualization of the documentary heritage) and the difference between them is minimal, the level of significance of the functions (priorities) being the hallmark of the book museum and library heritage divisions. In the attempt to determine the development of the book museum, the analysis of a directory on the development of museums, entitled Museums of Books and Bookmaking: International Directory, published in 1987 and regarded as historiographically valuable material, was undertaken. The information about universal European book museums provided in the above directory was compared with today’s situation. The conclusion has been drawn that an interest in book museums in the second half of the 20th century was a natural outcome of the development of book science of that time. The pace of establishing book museums was directly linked to the intensification of book science as a viable scientific discipline in European and global science. The topic of book museums in the field of the book science of those days was extremely popular. At the time, the largest number of book museums was in Germany (25), Great Britain (11), USA (10), the then Czechoslovakia (10), Italy (8), and Poland (5). It turned out that out of the 10 universal book museums which were functioning in the 70ies and 80ies of the 20th century, only five exist today. The others were closed down, narrowed down their activities or changed their profile altogether. Some museums have retained a very traditional academic character. Given the context of contemporary and modern museology, with all the attention focused on the visitor rather than on the museum objects themselves, the situation of these museums is problematic.
Keywords: museums, book museum, universal book museum, modern museum, library, documentary heritage, the old book, the book as a museum item